Effectiveness of dynamic neuromuscular stabilization training on strength, endurance, and flexibility in adults with intellectual disabilities, a randomized controlled trial - Hamed Babagoltabar-Samakoush; Behnoosh Aminikhah; Saeid Bahiraei (Scientific Reports)
Abstract Individuals with intellectual disabilities (ID) often exhibit lower levels of physical fitness compared to the general population, including reduced strength, endurance, flexibility, and coordination. Dynamic neuromuscular stabilization (DNS) training can potentially improve the performance of adults with ID caused by weak motor skills due to a lack of desirable nerve growth during childhood and before puberty. Also, DNS training proposed to improve physical fitness in this population, but the effectiveness and durability of DNS training on specific fitness components have not been well-established. This study employed a randomized controlled trial design to investigate the effects of an 8-week DNS training program on the strength, endurance, and flexibility of adults with ID. A total of 31 participants were randomly assigned to either an intervention group (n = 16) or a control group (n = 15). Muscular strength, endurance, and flexibility were assessed at baseline (pre-test), immediately after the intervention (post-test), and 2 months following the intervention (follow-up) using the 30-second chair stand (30sCS) test, sit-ups test, trunk lift test, and chair sit-and-reach test. Participants in the intervention group engaged in the DNS training program for 8 weeks, with 3 sessions per week, while the control group maintained their usual activities. The analysis of the outcome measures revealed significant time, group, and time-group interaction effects. Post-hoc analyses indicated that the DNS group exhibited significantly greater improvements in 30sCS, sit-ups, trunk lift, and chair sit-and-reach compared to the control group (p < 0.01). These improvements were maintained at the 2-month follow-up assessment in the DNS group. This randomized controlled trial demonstrates that an 8-week DNS training program significantly improves muscular strength, endurance, and flexibility in adults with ID, with benefits maintained at a 2 month follow-up. Further research is needed to replicate these findings and investigate underlying mechanisms, but the study highlights the potential of DNS training to promote physical fitness and well-being in individuals with ID. Trial registration RTC, prospectively registered in the Clinical Trial Registry (UMIN000053560) on 24/03/2024.